925 Safety of babies, children and youth. (1st September 2016) - Amann, Gregoria Paixão Von; Silva, Ines; Azevedo, Joana
Abstract : Background: Despite the large reduction of child mortality due to traffic collisions, safe and secure transportation of children from birth and through the life cycle, it continues being a concern of the Ministry of Health and the Ministry of Internal Affairs. For this common problem they join effort and under the auspicious of the Decade of Action of Road Safety, on 11 may 2011 launched a project aimed to improve safe transport of newborns since they leave Hospital maternity and along childhood. Methods: The National Road Safety Strategy reinforce strategic and operational objectives and the National Program of Injury Prevention develops a project called Safety of Babies, Children and Youth targets of reducing child mortality and serious injury and to increase the use of child restraint systems. For the implementation of the project we have a partnership with DOREL, a company that produces in Portugal child restraint systems and MAPFRE Foundation who developed a website on child road safety supports costs from training health professional and production of booklets and leaflets. The Portuguese Association for Child Safety Promotion, an NGO working in child safety give us their expertise in child restrains system and is also a partner of the project. Results: Currently we have 47 projects implemented in Hospital Maternity and Health Centres across the country, 6000 health professional involved and 60000 parents trained on how to use and use properly child restraints system. In the near future we will start working with the grandparents. Conclusions: The successful implementation of the project in the health services mobilised other actors that spontaneously joined us and are already engaged in community important aspects like control of the use of safety devices near schools and kindergartens by police forces and it's beginning a taxi drivers movement called 'taxis children's friends'.